"Os vulneráveis" - A luta e a resistência de permanecer na universidade - Sousa, Willy Cardoso (Universidade Federal do Tocantins, 2021)
With the experience of the researcher in the participation of the student movement of social work, as well as the completion of the mandatory internship for training in Social Work at the Dean of Student Affairs of the Federal University of Tocantins (PROEST-UFT), this monograph sought to know and reflect on the specificities of the National Student Assistance Program in meeting the demands of students, specifically, from the Federal University of Tocantins from the public basic education network. Through the socio-historical rescue, the work shown here, sought to highlight the trajectory of struggle, changes and resignifications of the Brazilian Social Work from the 1930s to the present. Counter-reforms, privatization, commercialization and expansion to Brazilian higher education processes, covering since the governments: Fernando Henrique Cardoso, Lula and Dilma, jointly addressing the attacks carried out by the genocidal, anti-democratic and fascist (de) government on universities and federal educational institutes higher. Although the student assistance policy is not considered an integral part of the academic education process, it does in a certain way guarantee: access, permanence, struggle and student success at the conclusion of the higher education course, so that it is prepared to the labor market. For the preparation of the referred work, a bibliographical and documentary research was carried out, using secondary sources previously selected, highlighting among them the use of books, academic articles and journalistic materials that could facilitate the understanding of the studied area.